Contribution of glial inwardly rectifying potassium (Kir) channels to potassium buffering in insect neural systems - Rui Chen; Zhilin Li; Alyssa Johnson; Daniel R. Swale (iScience)
Summary: There is a paucity of information pertaining to the fundamental roles of glia in insect central nervous system (CNS) function and in the maintenance of ionic gradients. Inward rectifier potassium (Kir) channels are known to drive K+ buffering in mammals, but cellular expression patterns and the physiological roles of neural or glial Kir channels in insects have remained undefined. We show that Kir2 channels are expressed in astrocyte-like glia (ALG) and subperineurial glia, and live-cell imaging indicated that ALG Kir channels are involved in Drosophila CNS function by providing a mechanism for K+ buffering. The inhibition of Drosophila ALG Kir channels reduced K+ buffering events and altered spontaneous neural firing changes to Drosophila behavior. These data confirm insect glia are active participants supporting CNS function and highlight a conserved evolutionary mechanism for K+ homeostasis in neural systems across mammals and insects.